Factors Influencing the Adoption Rate of Artificial Insemination Technology in Beef Cattle Breeders in Damai Village, Tanralili District, Maros Regency - Syarif Ilham; T Amrullah; Sultan (BIO Web of Conferences)
The development of beef cattle farming is currently not well developed, especially smallholder farming, this is due to the low interest of breeders in adopting artificial insemination technology, where AI is expected to be able to increase production and improve the genetics of beef cattle. The aim of this research is to examine the intensity of counseling, level of knowledge, skills and cost of artificial insemination influencing the level of adoption of artificial insemination technology among beef cattle breeders in Damai Village, Tanralili District, Maros Regency. The research was carried out from November 2022 to December 2022 in Damai Village, Tanralili District, Maros Regency. The type of research used in this research is quantitative explanatory, namely research to determine the relationship between the independent variables of counseling intensity, level of knowledge, skills and cost of artificial insemination on the dependent variable of AI technology adoption level. The number of samples used in this research was 68 respondents using random sampling techniques. In this research, multiple linear regression data analysis was used using the help of a data processing program, namely the SPSS program. Based on the results of the research and discussion in this study, a conclusion can be drawn, namely that in a joint test (simultaneous) the factors of counseling intensity, level of knowledge, skills and cost of artificial insemination have a significant influence on the level of adoption of artificial insemination technology. In the individual (partial) test, the factors of extension intensity, level of knowledge, skills did not have a significant influence and only the variable cost of artificial insemination had a significant influence on the level of adoption of artificial insemination technology among beef cattle breeders in Damai Village, Tanralili District, Maros Regency.